Sex chromosomal abnormalities associated with equine infertility: validation of a simple molecular screening tool in the Purebred Spanish Horse - Anaya, G. (2017)
Chromosomal abnormalities in the sex chromosome pair (ECAX and ECAY) are widely associated with reproductive problems in horses. However, a large proportion of these abnormalities remains undiagnosed due to the lack of an affordable diagnostic tool that allows for avoiding karyotyping tests. Hereby, we developed an STR (single-tandem-repeat)- based molecular method to determine the presence of the main sex chromosomal abnormalities in horses in a fast, cheap and reliable way. The frequency of five ECAXIinked (LEX026, LEX003, TKY38, TKY270 and UCDE0502) and two ECAY-Iinked (EcaYH12 and SRY) markers was characterized in 261 Purebred Spanish Horses to determine the efficiency of the methodology developed to be used as a chromosomal diagnostic tool. All the microsatellites analyzed were highly polymorphic, with a sizeable number of alleles (polymorphic information content > 0.5). Based on this variability, the methodology showed 100% sensitivity and 99.82% specificity to detect the most important sex chromosomal abnormalities reported in horses (chimerism, Turner’s syndrome and sex reversal syndromes). The method was also validated with 100% efficiency in 10 individuals previously diagnosed as chromosomally aberrant. This STR screening panel is an efficient and reliable molecular-cytogenetic tool for the early detection of sex chromosomal abnormalities in equines that could be included in breeding programs to save money, effort and time of veterinary practitioners and breeders.